Gender segregation in vocational education - Imdorf, Christian; Hegna, Kristinn; Reisel, Liza. (Bingley, U.K. : Emerald, 2015)
The gender segregated nature of vocational education (VET) has received little attention in the stratification literature, despite the well-known consequences of VET for differences in labour market outcomes, such as job placement, income and access to full-time employment. This book investigates the institutional contexts of gender segregation in VET from a comparative perspective, through a number of cross-national comparisons as well as more in-depth studies of Canada, Norway, Germany, Australia and Bulgaria. The various chapters tackle questions about occupational expectations, gendered pathways to applied fields of study, educational transitions, feminization of occupations and the relationship between educational choice and opportunity structures. We discuss the relationship between institutional contexts and gender-typing of educational programs, and whether VET system characteristics make a difference to occupational outcomes across countries. The book concludes with a chapter on education-to-employment transitions (based on a large scale comparative project on labour market entry) assessing the impact of vocational education on gendered labour market inequalities.
Gender inequalities at labor market entry : a comparative view from the eduLIFE project / Moris Triventi ... [et al.] -- Vocational training and gender segregation across Europe / Emer Smyth, Stephanie Steinmetz -- Educational systems and gender segregation in education : a three-country comparison of Germany, Norway and Canada / Christian Imdorf ... [et al.] -- Gender segregation in occupational expectations and in the labour market : international variation and the role of education and training systems / Steffen Hillmert -- Regional gender differences in vocational education in Bulgaria / Petya Ilieva-Trichkova, Rumiana Stoilova, Pepka Boyadjieva -- Explaining the dynamics of occupational segregation by gender : a longitudinal study of the German vocational training system of skilled crafts / Katarzyna Haverkamp, Petrik Runst -- The need for social approval and the choice of gender-typed occupations / Verena Eberhard, Stephanie Matthes, Joachim Gerd Ulrich -- Two sides of the same coin? Applied and general higher education gender stratification in Canada / Ashley Pullman, Lesley Andres -- Gender segregation in Australian science education : contrasting post-secondary VET with university / Joanna Sikora.
Print version record
Keywords: Social Science -- Gender Studies; Gender studies, gender groups; Vocational education -- Europe; Sex differences in education -- Europe; Labor market -- Europe